The Effects of Social Capital for the Management of Environment Cleanliness in Adipura Programme - Dwijatenaya, Ida Bagus Made Agung; Dewi, Mutiara Kartika (Jurnal Bina Praja, 2016)
Social capital is a decisive factor in the management of environment cleanliness in Adipura Programme. Tenggarong City in achieving clean city has attempted various strategies, including by considering the community social capital factor. Adipura Award for Tenggarong City is unsustainable, indicating that the role of community social capital is not yet optimized. This research aims to analyse the effects of social capital for the management of environmental cleanliness. The instrument used is the questionnaire. The sampling collection technique uses the simple random sampling method, with the sample of 100 respondents. The analysis instrument used to test the hypotheses is Product Statistics and Service Solution (SPSS) Program version 13.0 for windows. The research result shows that community social capital positively and significantly affects the management of environmental cleanliness. Trust element positively and significantly affects the management of environment cleanliness. Cooperation and social norm elements positively but not significantly affect the management of environment cleanliness. It is recommended to Kutai Kertanegara Government to always optimize the active role of community. Community Social Capital should be used optimally.